THE DECISION OF SALT FARMERS BEHAVIOR TO THE USE GEOMEMBRANE TECHNOLOGY USING FUZZY AHP (Case in Lembung Village, Galis District, Pamekasan Regency) - Fitrotin Nazizah; Rosihan Asmara; Agustina Shinta Hartati Wahyuningtyas (Agricultural Socio-Economics Journal, 2020)
Pamekasan regency is an area in Madura Island that has the potential to increase the quality and quantity of salt by recommending the use of geomembrane technology. This research will give recommendation of factor is the highest priority of salt farmer’s behavior decisions on the use of geomembrane technology. The method developed in this research are combination of AHP and Fuzzy AHP method. AHP is used to determine the consistency of judgments made by each respondent and Fuzzy AHP is used to determine the criteria weight and subcriteria to determine the highest priority criteria and subcriteria decisions. Priority results using FAHP obtained that highest priority factor the behavior decisions of salt farmers  towards the use of geomembrane technology at the level of farmers and agencies to technical aspects  is production result subcriteria, to economic aspects is profit of salt farmers subcriteria, to socio cultural aspect is geomembrane technology is corresponding government advice and to environment aspects is quality of salt